Natural Growth Factor: Platelet Rich Plasma Stimulates Proliferation of Fibroblast Cell Culture - Setiawati, Ernie Maduratna (Indonesian Journal of Tropical and Infectious Disease, 2010)
Platelet rich plasma(PRP) is a source of many natural growth factor that can modulate wound healing. PRP has become a  valuable adjunct in dentistry. Fibroblast cell in ligament periodontal play on important role in periodontal regeneration. The study was performed to investigate the influence PRP 10%–100% on the proliferation of fibroblast cell culture in vitro. A fibroblast culture was estabilished from baby hamster kidney (BHK-21) were tested on proliferation was measured with MTT assay after induced PRP 10–100%. We showed that PRP stimulate the proliferation of fibroblast, PRP 80% as the optimal choice to a good enough proliferative stimulus. PRP has proven to be effective at improving surgical results in periodontal surgery. PRP also show promise in periodontal regenerative medicine.